2022
DOI: 10.7150/ijbs.69141
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps mediate m6A modification and regulates sepsis-associated acute lung injury by activating ferroptosis in alveolar epithelial cells

Abstract: Neutrophil extracellular traps (NETs) production is a major strategy employed by polymorphonuclear neutrophils (PMNs) to fight against microbes. NETs have been implicated in the pathogenesis of various lung injuries, although few studies have explored NETs in sepsis-associated acute lung injury (SI-ALI). Here, we demonstrate a major contribution of NETs to the pathology of sepsis-associated ALI by inducing ferroptosis of alveolar epithelial cells. Using both in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 68 publications
2
81
1
Order By: Relevance
“…Cao et al [ 24 ] found that ferroptosis can significantly inhibit IL-1 after LPS induced mouse bone marrow-derived macrophages β , TNF- α , and IL-6, thereby alleviating systemic inflammatory response. Zhang et al [ 25 ] confirmed that ferroptosis can reduce the inflammatory cytokine IL-1 in the mouse model β horizontal effect. Li et al [ 26 ] showed that ferroptosis can reduce the risk of traumatic brain injury in mouse models IL-1 β , TNF- α , and IL-6.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…Cao et al [ 24 ] found that ferroptosis can significantly inhibit IL-1 after LPS induced mouse bone marrow-derived macrophages β , TNF- α , and IL-6, thereby alleviating systemic inflammatory response. Zhang et al [ 25 ] confirmed that ferroptosis can reduce the inflammatory cytokine IL-1 in the mouse model β horizontal effect. Li et al [ 26 ] showed that ferroptosis can reduce the risk of traumatic brain injury in mouse models IL-1 β , TNF- α , and IL-6.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…Many genetic and epigenetic alternations are related to the maintenance of endothelial function ( 36 ). There is increasing evidence that sepsis-related pulmonary microvascular leakage and organ damage/dysfunction are associated with changes in epigenetics and gene expression ( 37 ). Chemical modification of RNA molecules is crucial for the post-transcriptional regulation of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of neutrophil extracellular traps (NETs) is the main strategy of polymorphonuclear neutrophils (PMN) against microorganisms. NETs are closely related to the pathogenesis of various lung injuries, but relatively little is known about the role of NETs in SA-AKI ( 37 ). Elevated levels of NETs and ferroptosis can be observed in infected ARDS patients and SA-AKI mice.…”
Section: Resultsmentioning
confidence: 99%
“…All these studies suggest that ferroptosis is involved in the development of ALI disease pathology. Ferroptosis may regulate ALI through neutrophil extracellular traps mediate m 6 A modification [122]. The future development of additional drugs or potential targets is essential for the treatment of ALI by targeting ferroptosis.…”
Section: Alimentioning
confidence: 99%